Safety and efficacy of treatment of very small intracranial aneurysms - Jamróz, Tomasz (Pol J Radiol, 2019)
PURPOSE: Very small intracranial aneurysms (VSIAs) may cause many neurological complications and even death. Thanks to technological progress and higher quality of non-invasive neuroimaging methods, these pathologies can be investigated sooner and treated earlier. Due to the controversy surrounding invasive treatment of these pathologies, the aim of the study was to analyse methods of treatment, their outcome, and complications in a group of patients with VSIAs. MATERIAL AND METHODS: Out of 444 cases of intracranial aneurysms treated in our centre, 65 aneurysms met the radiological criteria of VSIAs. The parameters – width and length of the aneurysm’s neck and width, length, and height of the aneurysm’s dome – were measured. The analysed parameters were as follows: symptoms upon admission and after treatment, days in hospital, and intraoperative complications. Clinical and radiological intensity of subarachnoid haemorrhage (SAH) was evaluated by using the Hunt-Hess and Fisher scales. The degree of embolisation of the aneurysm after the procedure was assessed using the Montreal Scale. Clinical outcome was assessed by Glasgow Outcome Scale. RESULTS: 50.77% of VSIAs were treated with endovascular procedures and 49.23% with neurosurgical clipping. SAH was presented in 38.46% of patients with VSIAs. Intraoperative complications were presented in 16.92% of patients with VSIAs, and the most common complication was ischaemic stroke. Stents were used in 51.52% of VSIAs. In 69.70% of embolisation procedures at VSIAs complete obliteration was achieved. The average result in the Montreal Scale was 1.31 (SD = 0.66). CONCLUSION: VSIAs can be treated as effectively and safely as larger aneurysms, by both endovascular and surgical methods.